SOLIDIFIKASI DAN STABILISASI BAHAN BUANGAN KERAK BAJA DARI INDUSTRI BAJA MALAYSIA - Salmiati Yunus (Purifikasi, 2005)
The study was conducted to test steel’s slag wasted from Malaysia’s steel industry as concrete using solidification/ stabilization method (S/S). The concrete was tested using pressurized test and Toxicity Characteristic Leaching Procedure (TCLP). Ions that were tested were Cd, Cu, Cr3+, Cr6+, Fe, Pb, Mn, S, Zn and Ni. After TCLP procedure, all ion concentration were under threshold limit issued by the Jabatan Alam Sekitar (JAS) standard. Ion concentration Al, Cu, Cr6+, Fe, Mn and Ni were increased along with curing age. Meanwhile, Cd and Pb ions were decreased along with curing age. Based on compressive test, mortar that contain steel slag were more stronger than control mortar in every curing age. This research concluded that steel slag in Malaysia’s industrial steel could be used as alternative building material.